2019
DOI: 10.3390/ijms20153696
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of STAT3, β-Catenin, and Notch-1 by Single and Combinations of siRNA Treatment Enhance Chemosensitivity of Wild Type and Doxorubicin Resistant MCF7 Breast Cancer Cells to Doxorubicin

Abstract: Combinatorial therapeutic strategies using siRNA and small molecules to eradicate tumors are emerging. Targeting multiple signaling pathways decreases the chances of cancer cells switching and adapting new signaling processes that may occur when using a single therapeutic modality. Aberrant functioning of Notch-1, Wnt/β-catenin, and STAT3 proteins and their crosstalk signaling pathways have been found to be involved in tumor survival, drug resistance, and relapse. In the current study, we describe a therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 63 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…Accumulating evidence has shown that Stat3 signalling is involved in breast cancer initiation and progression. Inhibition of the activity of Stat3 has become a popular therapeutic strategy (Zhang et al, 2010;Li et al, 2011;Alshaer et al, 2019;Xie et al, 2019). Therefore, the aim of this study was to explore the mechanisms of a novel small molecule inhibitor, Statmp-151, in breast cancer cells and provide support for the treatment of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has shown that Stat3 signalling is involved in breast cancer initiation and progression. Inhibition of the activity of Stat3 has become a popular therapeutic strategy (Zhang et al, 2010;Li et al, 2011;Alshaer et al, 2019;Xie et al, 2019). Therefore, the aim of this study was to explore the mechanisms of a novel small molecule inhibitor, Statmp-151, in breast cancer cells and provide support for the treatment of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Stattic is one of the classic inhibitors of Stat3 but is limited by low activity, low selectivity and high toxicity (Zhang et al, 2010). Ligustrazine is an alkaloid found in nature whose structure is simple and easy to modify (Alshaer et al, 2019;Xie et al, 2019). Ligustrazine has good pharmacokinetic properties, fast absorption, broad distribution and no cumulative toxicity (Cheng et al, 2007;Wu et al, 2013;Zeng et al, 2013;Han et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Notch1 was reported to involve in the malignant phenotype of RB 12,31 and chemosensitivity of multiple tumors. [32][33][34][35][36] The results of RT-qPCR and Western blot showed that Notch1 was significantly upregulated in RB cells (p < 0.05) ( Figure 1A and B). However, the upstream miR regulating Notch1 expression remained unclear.…”
Section: Notch1 Was Upregulated In Rb Cells and Mir-515-5p Inhibitedmentioning
confidence: 99%
“…The FZD3 protein is mapped to chromosome 8p21, a major component of the Wnt signaling pathway, which is involved in regulating early neural development [81]. The 5′-tiRNA Val can directly bind to FZD3 and inhibit FZD3-mediated Wnt/β-catenin pathway [18], which is related to tamoxifen and doxorubicin resistance [82,83]. In addition, the downregulation of FZD3 significantly reduces the expression of cyclin D1 and c-myc [18].…”
Section: Mechanisms Of Breast Cancer Resistance Related To Trfs and Tmentioning
confidence: 99%